Preventing fraud in village financial management: the role of competence, systems, and anti-fraud awareness - Mega, Katryn Natania; Tinangon, Jantje J.; Walandouw, Stanley Kho (Yayasan Widyantara Nawasena Raharja, 2025)
Fraud is an illegal act in the form of deception, concealment, or violation of trust committed by a person or organization with the aim of obtaining money, property, services, or to protect personal or business interests. Prevention of fraud needs to be done so that the organization, in this case the village government, does not suffer losses. The purpose of this study is to examine and analyze the influence of the competence of village apparatus and the village financial system on fraud prevention, as well as to examine and analyze whether anti-fraud awareness can moderate the influence of the competence of village apparatus and the village financial system on fraud prevention. This research was conducted in villages in East Bolaang Mongondow Regency, with all village heads and finance heads as respondents. The data analysis process to determine the results for outer model testing, inner model testing, and hypothesis testing. The results of this study are that the village apparatus competence and the village financial system have a significant positive effect on fraud prevention. This means that the higher the competence of village apparatus and the better the implementation of the village financial system application, the greater the prevention of fraud. The next result is that anti-fraud awareness strengthens the influence of village apparatus competence on fraud prevention. However, anti-fraud awareness weakens the influence of the village financial system on fraud prevention.